2018
DOI: 10.1021/acs.energyfuels.7b03647
|View full text |Cite
|
Sign up to set email alerts
|

Petrological Characteristics and Trace Element Partitioning of Gasification Residues from Slagging Entrained-Flow Gasifiers in Ningdong, China

Abstract: In order to better understand the petrological characteristics of gasification residues and trace element partitioning during entrained-flow gasification processes, oil-immersion microscopy, X-ray diffraction, scanning electron microscopy combined with an energy dispersive detector, inductively coupled plasma mass spectrometry, a Milestone DMA-80 Hg analyzer, and pyrohydrolysis in conjunction with a fluorine ion-selective electrode were employed to study samples collected from three commercial-scale slagging e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 106 publications
0
19
0
Order By: Relevance
“…Ningdong energy and chemical base is one of the most advanced bases for developing clean coal technology in China. In 2018, the base generated nearly 8 million tons of CGS [3]. At present, there is no good treatment method, and it can only be landfilled after high-standard anti-seepage treatment on the ground, which is quite different from the systematic utilization of fly ash [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ningdong energy and chemical base is one of the most advanced bases for developing clean coal technology in China. In 2018, the base generated nearly 8 million tons of CGS [3]. At present, there is no good treatment method, and it can only be landfilled after high-standard anti-seepage treatment on the ground, which is quite different from the systematic utilization of fly ash [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…At present, there are many researches on the resource utilization of fly ash and slag in the world [7,8,10]. However, since the CGS is obtained in a high-pressure vaporization furnace under a reducing atmosphere (CO, H 2 ) and 1400-1500 • C, its structure and composition are greatly different from those of fly ash and slag [3,5,9]. Therefore, it is difficult to realize the utilization of CGS by the same method.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authoritative background values of trace elements in Chinese coals were obtained by Dai et al (2012a, b) and an evaluation formula of enrichment coefficients of trace elements was established by Dai et al (2014). Recently, the emphases of researches on trace elements are on their behavior during coal utilization (Tang et al 2018a;, their health impacts (Dai et al 2014;Finkelman and Tian 2018), and recovery of valuable trace elements (Dai et al 2006b;Seredin and Dai 2012;Dai et al 2014Dai et al , 2016Dai and Finkelman 2017). This last topic is illustrated by the fact that germanium has achieved industrial extraction (Tang and Huang 2004).…”
Section: Trace Elements In Coalmentioning
confidence: 99%
“…In the GE-FR, more than 60% of the Cr was in the carbonates and iron and manganese oxides (likely calcite or some oxidized species), while about 70% of the Cr was in the sulfides in the GSP-FR ( Figure 14A,B). Tang et al [40] showed that spinel was identified in the gasification residues, but Cr-bearing spinel was not determined by SEM-EDX due to the low concentration of Cr. In this study, Cr identified in the carbonates and iron and manganese oxides is probably associated with spinel (note that spinel was not identified by XRD or SEM-EDX).…”
Section: Chromium (Cr)mentioning
confidence: 99%